2021
DOI: 10.1111/jfpp.15865
|View full text |Cite
|
Sign up to set email alerts
|

Production of Sacha Inchi oil emulsions by high‐shear and high‐intensity ultrasound emulsification: Physical properties and stability

Abstract: Sacha Inchi (Plukenetia volubilis L.) is a plant of the Euphorbiaceae family with a great economic expansion in Central and South America, as well as in some South-East Asiatic countries (Gutiérrez et al., 2019).This promising crop has potential industrial applications in foods, pharmaceuticals, and cosmetics, since their fruits (shell-covered kernels) are a good source of oil (35%-60%) rich in polyunsaturated fatty acids and tocopherols (Gutiérrez et al., 2017). The main fatty acids of Sacha Inchi oil (SIO) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…It is worth mentioning that increasing the power and time of sample processing above a certain threshold negatively affects the emulsion stabilization properties [ 29 ]. The rheological properties of sacha inchi oil emulsions were studied by González-Cardozo et al [ 16 ], who found that the emulsions are shear-thinning fluids. However, the emulsifiers used were maltodextrin and a modified starch, which may have had an influence on the slope and shape of the curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that increasing the power and time of sample processing above a certain threshold negatively affects the emulsion stabilization properties [ 29 ]. The rheological properties of sacha inchi oil emulsions were studied by González-Cardozo et al [ 16 ], who found that the emulsions are shear-thinning fluids. However, the emulsifiers used were maltodextrin and a modified starch, which may have had an influence on the slope and shape of the curve.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Urbánková et al [ 15 ] used a natural casein-based emulsifier to emulsify with tamanu oil, but this is the only paper describing the properties of such a system, in addition to not addressing the rheological properties of the emulsion. In the case of inca inchi oil, the only paper on its emulsion with natural stabilizers (maltodextrin and a modified starch) is that published by González-Cardozo et al [ 16 ]. This scarcity of work demonstrates the need for more research on emulsions of the aforementioned oils stabilized with natural emulsifiers, which would allow their use in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Tanaman sacha inchi banyak digunakan pada berbagai industri makanan dan farmasi (Luis et al, 2011) serta dapat dijadikan industri pangan berkelanjutan (Kodahl, 2022). Minyak yang terkandung dalam tanaman sacha inchi mempunyai stabilitas yang tinggi (Lina et al, 2021), lebih lanjut asam lemak esensial terutama omega 3 dan omega 6 yang terkandung di dalamnya juga sangat baik digunakan untuk suplemen makanan (Ramos et al, 2019). Melihat besarnya potensi dari tanaman sacha inchi ini maka perlu adanya upaya produksi yang berkelanjutan.…”
Section: Pendahuluanunclassified
“…However, the development of sacha inchi in Indonesia is still limited as cultivation locations only exist in a few areas and people are not familiar with the potential of this plant, which suggests a low interest in cultivating it. One of the most important things in the production of modern agriculture is fertilization [20,21]. Based on research by Z.Q.…”
Section: Introductionmentioning
confidence: 99%